National Integrated Network For Remote Monitoring Of Patients In Benin - MEDENOU, DATON; AHOUANDJINOU, Mêtowanou Héribert; HOUESSOUVO, C. Roland (My University, 2019)
The Benin health system has challenges including: (i) the need to provide quality health care at low cost to a growing population, (ii) the reduction of patients' hospitalization time, (iii) and the optimization presence time of the nursing staff. Such challenges can be solved by remote monitoring of patients. Methodology: To achieve this, five steps were followed. 1) The identification of the different characteristics of the WBAN systems and the physiological parameters monitored on a patient. 2) The modeling of the national RIMP architecture in a cloud of Technocenters. 3) Cross analysis between characteristics and functional requirements identified. 4) The simulation of the functionality of each Technocenter through: a) the choice of design approach inspired by the life cycle of V systems; b) functional modeling through SysML Language; c) the study of the choice of communication technology and different architectures of sensor networks. 5) An estimate of the material resources of the national RIMP according to physiological parameters. Findings: The main result is that it has designed a National Integrated Network for Patient Monitoring (RNIMP) remotely, ambulatory or not, for the Benin health system. Conclusion: The implementation of the RNIMP will contribute to improve the care of patients in Benin. The proposed network is supported by a repository that can be used for its implementation, monitoring and evaluation. It is a table of 36 characteristic elements each of which must satisfy 5 requirements relating to: medical application, design factors, safety, performance indicators and materiovigilance.
Keywords: architecture; requirements; hospital; patient; repository; RNIMP; simulation; SysML; system; technocenter.